The role of software intellectual property rights in strengthening industry performance: Evidence from South Korea - Dukrok Suh; Dong-hyun Oh (Elsevier Inc., 2015)
This paper investigates the effects of software intellectual property rights (IPRs) on the performance of software firms. For this, technical efficiency scores for Korean software firms are examined, and for an empirical analysis, data envelopment analysis (DEA) and stochastic frontier analysis (SFA) methods are employed for robust results. Firm-level data from the Korean software industry on software copyrights and patents for the 1995 ？2005 period are employed. According to the empirical results, software IPRs increase the technical efficiency of software firms. Policy implications are given based on the results of our empirical analysis.